Development of Student Collaboration Skills In Learning Mathematics Through A Lesson Study Approach - La Misu; Hasnawati; Salim; Wa Ode Indrawati (Jurnal Amal Pendidikan, 2023)
The purpose of this research is: to see the development of students' collaboration skills in learning mathematics through the Lesson Study approach in the Mathematics Education Study Program. This type of research is descriptive research with a qualitative approach. The subjects of this research were students of the Mathematics Education Study Program at Halu Oleo University, who were enrolled in the Kapita Selecta Mathematics course. The implementation of this research consists of 3 cycles, and each cycle consists of 3 stages, namely preparation, implementation, monitoring and evaluation. The method used in this research consists of 3 stages, namely plan, do, and see. Data collection techniques in this study include two kinds of instruments, namely the main instrument and supporting instruments. The data analysis technique follows the Miles, Huberman, and Saldana analysis model, consisting of three activities that occur simultaneously: data condensation, data presentation, and conclusion drawing/verification. The result of this research is the development of students' collaboration skills in learning mathematics through Lesson Study approach in Mathematics Education Study Program. Generally, there is an increase in student learning outcomes in mathematics learning with the Lesson study approach, namely for Cycle 1, average 83.0; Cycle 2, average 78.0; and Cycle 3; average 85.0.